Aliran Permukaan, Erosi dan Kehilangan Hara Kebun Kelapa Sawit Kabupaten Sorolangun Provinsi Jambi: Surface runoff, Soil erosion and Nutrient Losses in Oil Palm Platation Sorolangun District, Jambi Province - Novia Mustikasari; Suria Darma Tarigan; Supiandi Sabiham; Bandung Sahari (Jurnal Ilmu Tanah dan Lingkungan, 2018)
Loss of nutrients through surface runoff and erosion carried from agricultural land, is a major cause of agricultural land degradation. The purpose of this study was to analize nutrients loss from oil palm plantation caused by erosion. This study was carried out using erosion plots measuring 12 m x 3 m consisting a combination of two factors: type of oil palm inter-row and slope. Surface runoff and erosion values in the active inter-row was higher than those in death inter-row. The nutrients loss of N, P, and K from soil eroded in active inter-row were respectively 0.04; 0.11 and 0.10 ton ha-1 year-1. The total nutrient losses (N, P, K) in dead inter-row were 0.007; 0.024 dan 0.023 ton ha-1 year-1.